2007
DOI: 10.1002/app.26424
|View full text |Cite
|
Sign up to set email alerts
|

Impact of impregnation with boron compounds on the surface hardness of varnished wood

Abstract: This study was performed to determine the impact of impregnation with boron compounds on the surface hardness of varnished wood materials. For this purpose, test specimens prepared from Oriental beech (Fagus orientalis Lipsky) and oak (Quercus petreae Lipsky), which met the requirements of ASTM D 358, were impregnated according to ASTM D 1413 with boric acid and borax by a vacuum technique. After impregnation, the surfaces were coated by cellulosic, synthetic, polyurethane, waterborne, acrylic, and acid harden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…Therefore, it was concluded that boron compounds increase the surface hardness of the varnished wood [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it was concluded that boron compounds increase the surface hardness of the varnished wood [8]. …”
Section: Introductionmentioning
confidence: 99%
“…After the varnishing process, the layer hardness of the samples was determined. According to this; the highest in terms of hardness value, wood type, impregnation material and varnish type interaction; sessile oak+borax+acrylic varnish, lowest; Obtained in oak+borax+synthetic varnish [37]. The hardness value, water-based varnish + nano silver interaction, was found to be 8% lower in Oriental beech, 12% higher in Oak compared to the control samples and it did not show any effect in Scots pine.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have explained that the wood hardness increased after impregnation. Boric acid and borax increased the hardness of varnished wood surface (Ors et al 2007). Malik and Ozarska (2019) reported that the density and hardness of white jabon wood ( Anthocephallus cadamba ) increased after impregnation with polymerized merbau extractives.…”
Section: Resultsmentioning
confidence: 99%